A Review on Cooling Performance of Vertical Green System for Green Facade and Living Wall - Cathla, Damian Andrew; Ismail, Isham (Recent Trends in Civil Engineering and Built Environment, 2024)
The rapid development and population cause the increasing of surrounding temperature cause Urban Heat Island (UHI) which this situation gets serious in tropical region lead to alternative solution that is the using of Vertical Green System on the building. This review is reviewing on cooling performance of Vertical Green System (VGS) as one of the alternatives to curb warm surrounding especially in hot climate. The aim of this review is studying the cooling performance and effectiveness of living wall and green façade plus the review is emphasize on cooling performance by Vertical Green System of living wall and green façade. The data for review is using previous research that obtain from online platform through ProQuest, Science Direct, MyTO, and UTHM PTTA Digital Archive. The previous data find that the VGS of living wall and green façade cooling effect can up to 2.5˚C in cold weather and 13˚C in hot weather with average of 1.4% increasing of Relative Humidity (RH). It can be conclude the cooling performance of VGS is that the increases of humidity cause temperature to decrease.